2020
DOI: 10.1002/ppap.202000171
|View full text |Cite
|
Sign up to set email alerts
|

An overview of low‐temperature plasma surface modification of carbon materials for removal of pollutants from liquid and gas phases

Abstract: As a promising surface treatment technique, low‐temperature plasma (LTP) technology has been widely used over the past two decades. Herein, the surface modification of carbon materials using LTP treatment is reviewed to clarify the modification effects. First, the basic details of LTP treatment are summarized. Second, the surface morphology, pore structure, surface chemistry, adsorption performance, and catalytic characteristics of LTP‐treated carbon materials are reviewed. Finally, the research required to fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 161 publications
1
21
0
Order By: Relevance
“…The possible mechanism of surface activation could be divided into the presented steps in Figure e. The high-energy active species (HASs) generated by plasma, including free radicals, excited molecules or atoms, positive ions, and electrons, first attack the carbon surface and result in a high-energy surface. , Then, the highly reactive N and O plasma reacts with the high-energy CF surface and form different functional groups . The possible functional groups inferred from the XPS results are CO, O–CO, pyridinic-N, pyrrolic-N, and graphitic-N, as illustrated in Figure e.…”
Section: Resultsmentioning
confidence: 99%
“…The possible mechanism of surface activation could be divided into the presented steps in Figure e. The high-energy active species (HASs) generated by plasma, including free radicals, excited molecules or atoms, positive ions, and electrons, first attack the carbon surface and result in a high-energy surface. , Then, the highly reactive N and O plasma reacts with the high-energy CF surface and form different functional groups . The possible functional groups inferred from the XPS results are CO, O–CO, pyridinic-N, pyrrolic-N, and graphitic-N, as illustrated in Figure e.…”
Section: Resultsmentioning
confidence: 99%
“…[20] There have been some latest researches on plasma-modified carbon materials, which found that plasma modification could increase the adsorption capacity of metal ions. [21] For example, when biochar was treated with NH 3 plasma, the emission intensity of NH species on the surface of the biochar showed a dependency on the discharge intensity. [22] O 2 and N 2 plasma modification enhanced the formation of oxygen-containing functional groups and nitrogen-containing functional groups on Activated carbon (AC) surface, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly due to the numerous applications of cold atmospheric plasma (CAP), including in liquid media [ 3 , 4 ]. The liquid–CAP interaction is being increasingly studied due to its importance in applications such as nanoparticle (NP) synthesis [ 3 , 5 ], environmental remediation [ 6 ], sterilization [ 7 ], agriculture [ 8 ], biology [ 9 ], medicine [ 10 , 11 , 12 , 13 ], and food [ 14 , 15 , 16 ]. These and other applications are possible due to the generation of UV radiation, shock waves, and active radicals from the plasma, whose reaction product with the liquid is, almost always, the precursor of the modification of material properties [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%